Outpatient percutaneous nephrolithotomy in a renal transplant patient: World’s first case - McAlpine, Kristen; Leveridge, Michael J.; Beiko, Darren (Canadian Urological Association Journal, 2015)
Percutaneous nephrolithotomy (PCNL) is an established safe and effective surgical treatment option for renal calculi in renal allografts. The advent of tubeless PCNL has led to reports of ambulatory or outpatient PCNL. This case report describes the successful outpatient management of a 49-year-old female with a symptomatic renal pelvic calculus in her transplanted kidney. Tubeless PCNL successfully removed the stone, free of complication, and the patient was discharged 2 hours and 17 minutes after the procedure in stable condition with minimal pain. This is, to the best of our knowledge, the first successful case of outpatient tubeless PCNL in a transplanted kidney.